Estimating transmission dynamics of African swine fever virus from experimental studies. Issue 6 (26th November 2022) - Main, Alastair Ronald; Halasa, Tariq; Olesen, Ann Sofie; Lohse, Louise; Rasmussen, Thomas Bruun; Belsham, Graham J.; Boklund, Anette; Bøtner, Anette; Christiansen, Lasse Engbo
Abstract: African swine fever virus (ASFV) continues to spread across the world, and currently, there are no treatments or vaccines available to combat this virus. Reliable estimates of transmission parameters for ASFV are therefore needed to establish effective contingency plans. This study used data from controlled ASFV inoculations of pigs to assess the transmission parameters. Three models were developed with (binary, piecewise‐linear and exponential) time‐dependent levels of infectiousness based on latency periods of 3–5 days derived from the analysis of 294 ethylenediamine tetraacetic acid–stabilized blood samples originating from 16 pigs with direct and 10 pigs with indirect contact to 8 inoculated pigs. The models were evaluated for three different discrete latency periods of infection. The likelihood ratio test showed that a binary model had an equally good fit for a latency period of 4 or 5 days as the piecewise‐linear and exponential model. However, for a latency period of 3 days, the piecewise‐linear and exponential models had the best fit. The modelling was done in discrete time as testing was conducted on specific days. The main contribution of this study is the estimation of ASFV genotype II transmission through the air in a confined space. The estimated transmission parameters via air are not much lower than for direct contact between pigs. The estimated parameters should be useful for future simulations of control measures against ASFV.